The Effect of the Assistance Model on Adherence to Treatment of Drug Resistant Tuberculosis (RO TB) Patients - Winarti Rinawati, Sri Arini; Palestin, Bondan; Ardesa, Yopi Harwinanda (Caring : Jurnal Keperawatan, 2024)
ABSTRACT Background: Drug resistant Tuberculosis (TB RO) patients need external support from others in the form of patient assistance in order to realize quality and patient-centered TB services. Objective: Knowing the results of the influence of the mentoring model on TB RO patients in DIY. Method: Is a quasi-experimental study of 30 RO TB patients in the Special Region of Yogyakarta, with the aim of knowing the level of knowledge and demographic characteristics of RO TB patients. This research has been declared ethically feasible based on KEPK Number e-KEPK / POLKESYO / 0619 / VIII / 2022. Result: TB RO patients are mostly ? 45 years old with male gender. There was a relationship between knowledge of adherence to RO TB treatment as evidenced by pearson tests showing significant results between the two variables, with a p value = 0.000 (<0.01). The mentoring model carried out has a significant influence on adherence to RO TB treatment. As evidenced by the results of mann Whitney's test and analysis, there is a value of 0.037 (<0.05). Conclusion: Knowledge provides a significant impact on adherence to RO TB treatment.       INTISARI Latar Belakang: Pasien Tuberkulosis resisten obat (TB RO) memerlukan dukungan eksternal yang berasal dari orang lain berupa pendampingan pasien agar dapat mewujudkan pelayanan TB yang berkualitas dan berpusat pada pasien. Tujuan: Mengetahui hasil pengaruh model pendampingan kepada pasien TB RO di DIY. Metode: Merupakan studi quasi eksperimen terhadap 30 pasien TB RO di wilayah Daerah Istimewa Yogyakarta, dengan tujuan mengetahui tingkat pengetahuan dan karakateristik demografi pasien TB RO. Penelitian ini telah dinyatakan layak secara etik berdasarkan KEPK Nomor e-KEPK/POLKESYO/0619/VIII/2022. Hasil: Pasien TB RO sebagian besar berusia ? 45 tahun dengan jenis kelamin laki-laki. Terdapat hubungan antara pengetahuan terhadap kepatuhan pengobatan TB RO yang dibuktikan dengan uji pearson menunjukkan hasil signifikan antara kedua variabel tersebut, dengan nilai p= 0.000 (<0.01). Model pendampingan yang dilakukan memberikan pengaruh yang signifikan terhadap kepatuhan pengobatan TB RO. Dibuktikan dengan hasil uji dan analisis Mann Whitney, terdapat value sebesar 0.037 (<0.05). Kesimpulan: Pengetahuan memberikanpengaruh yang signifikan terhadap kepatuhan pengobatan TB RO.